Biologics in ocular inflammatory diseases – Experience from a tertiary referral eye care center in South India - Kalpana Babu; PG Padmapriya; Anand P Rao; Ramesh Jois (Indian Journal of Ophthalmology)
Purpose: To analyze the utility of biologics in noninfectious uveitis and other ocular inflammatory diseases in a South Indian patient population. Methods: This was a retrospective observational study conducted at the uveitis and ocular inflammatory diseases clinic of a tertiary eye care hospital in South India between 2016 and 2023. Results: Records of 76 patients on biologics were retrieved from our databases. The mean age was 34.84 ± 17.383 years. In 75% of patients, the duration of follow-up was 52.75 months. Overall, anterior nongranulomatous uveitis was the most common anatomic type of uveitis (34.21%). HLA B27-associated uveitis was the most common etiology (34.21%) in whom biologics were used. Patients <18 years of age formed 23.7% with a mean age of 10.77 ± 2.75 years. Mean duration of follow-up in patients <18 years of age was 36 months. In this subgroup, panuveitis was the most common anatomic subtype (61.1%) and juvenile idiopathic arthritis was the most common etiology (27.7%). The most commonly used biologic in this study was adalimumab (36.84%). Additional conventional immunomodulators were used along with biologics in 50 patients (65.78%), of which methotrexate was the most common (50%). Adalimumab and rituximab were biosimilars, while tofacitinib was the generic version. There was a significant decrease in the mean number of flareups post-biologics (P = 0.001). Adverse effects were seen in 14 patients (18.42%). The success rate of biologics was low in the parsplanitis group <18 years (33.3%), Blau-associated uveitis (50%), and idiopathic uveitis (30%). Conclusion: In this study, we have analyzed the results of biologics in different anatomic types of ocular inflammation and etiologies. The success rate of biologics was low in parsplanitis, idiopathic uveitis, and Blau-associated uveitis and higher in other etiologies.